Vitamin D (1_,25(OH)2D3) supplementation minimized multinucleated giant cells formation and inflammatory response during Burkholderia pseudomallei infection in human lung epithelial cells - Pohnratchada Mattrasongkram; Saharut Wongkaewkhiaw; Suwimol Taweechaisupapong; Sorujsiri Chareonsudjai; Teerasit Techawiwattanaboon; Thararin Ngamsiri; Sakawrat Kanthawong (My University, 2023)
Melioidosis is an infectious disease with high mortality rates in human, caused by the bacterium Burkholderia pseudomallei . As an intracellular pathogen, B . pseudomallei can escape from the phagosome and induce multinucleated giant cells (MNGCs) formation resulting in antibiotic resistance and immune evasion. A novel strategy to modulate host response against B . pseudomallei pathogenesis is required. In this study, an active metabolite of vitamin D 3 (1α,25-dihydroxyvitamin D 3 or 1α,25(OH) 2 D 3 ) was selected to interrupt pathogenesis of B . pseudomallei in a human lung epithelium cell line, A549. The results demonstrated that pretreatment with 10 −6 M 1α,25(OH) 2 D 3 could reduce B . pseudomallei internalization to A549 cells at 4 h post infection ( P < 0.05). Interestingly, the presence of 1α,25(OH) 2 D 3 gradually reduced MNGC formation at 8, 10 and 12 h compared to that of the untreated cells ( P < 0.05). Furthermore, pretreatment with 10 −6 M 1α,25(OH) 2 D 3 considerably increased hCAP-18/LL-37 mRNA expression ( P < 0.001). Additionally, pro-inflammatory cytokines, including MIF, PAI-1, IL-18, CXCL1, CXCL12 and IL-8, were statistically decreased ( P < 0.05) in 10 −6 M 1α,25(OH) 2 D 3 -pretreated A549 cells by 12 h post-infection. Taken together, this study indicates that pretreatment with 10 −6 M 1α,25(OH) 2 D 3 has the potential to reduce the internalization of B . pseudomallei into host cells, decrease MNGC formation and modulate host response during B . pseudomallei infection by minimizing the excessive inflammatory response. Therefore, 1α,25(OH) 2 D 3 supplement may provide an effective supportive treatment for melioidosis patients to combat B . pseudomallei infection and reduce inflammation in these patients.
Keywords: Burkholderia pseudomallei; Melioidosis; Burkholderia infections and melioidosis